PENERAPAN METODE ROLE PLAYING DALAM PROSES PEMBELAJARAN - Junaidah (AZKIA : Jurnal Aktualisasi Pendidikan Islam, 2022)
The learning method is a method or procedure used to facilitate the implementation of the learning process in the learning environment. One method that can be applied in the learning process is the Role Playing method. The Role Playing method is a method that can develop the imagination and appreciation carried out by students by playing them as living figures or inanimate objects. The application of this learning method aims to train students in socializing because this method involves students pretending to play roles/characters involved in the historical process or community behavior, for example how to inspire people to keep the environment clean, and so on. In addition, the Role Playing method provides opportunities for students to be able to work well together, and students are required to express their opinions according to the time available. This method is very good applied in the classroom because it can help students be active and creative so that learning is interesting and fun.